Enhancing Teacher Competence through Principal Managerial Competence in the Planning of Inclusive Education in Elementary Schools - Mayasari, Dina; K, Karlimah; Mulyadi, Sima (Universitas Pendidikan Indonesia (UPI), 2024)
Implementing an inclusive approach in elementary schools helps provide a learning environment that accommodates the needs of all students. This study aimed to examine the principal's competence when planning inclusive education programs to enhance teachers' performance in Ciamis Regency's elementary schools. The research methodology employed in this study was a case study approach, utilizing data collection approaches such as interviews, observations, and documentation analysis. The results of this study indicate that effective program planning necessitates the presence of a well-defined plan, and it is imperative for every principal to develop the strategic plan in order to execute the planned program successfully. There needs to be an individual responsible for overseeing the program implementation process and ensuring that the principal remains focused on the activities related to inclusion procedures. The principal's role as an educational planner in inclusive schools involves meticulous academic preparation for the annual program, semester program, and evaluation, which enables effective management. Principals oversee, advise, and administer human resources, facilities, and infrastructure. They cultivate a nurturing school climate, offer guidance to school staff, and implement engaging, inclusive learning approaches. At last, when it comes to educational planning, principals have effectively developed programs, services, infrastructure, and coaching to enhance teachers' performance in inclusive schools.